The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1007/s00299-009-0792-1
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces scabiei and its toxin thaxtomin A induce scopoletin biosynthesis in tobacco and Arabidopsis thaliana

Abstract: Streptomyces scabiei is the predominant causal agent of common scab of potato in North America. The virulence of common scab-causing streptomycetes relies on their capacity to synthesize thaxtomins. In this study, the effects of S. scabiei infection and of thaxtomin A, the main toxin produced by S. scabiei, were tested for the elicitation of plant defense molecules in the model plants tobacco (Nicotiana tabacum) and Arabidopsis thaliana. Tobacco leaves infected with spores of S. scabiei strain EF-35 or infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
0
34
0
3
Order By: Relevance
“…Susceptible cultivars produce non-uniform deposits of suberin making them less performing against pathogens (Finetti Sialer 1990;Ray and Hammerschmidt 1998). The anti-microbial agents produced by potatoes can be glycoalkaloids (α-chaconin and α-solanine), phenolic compounds and phytoalexins, antimicrobial compounds produced by the plant after pathogen attacks (Okopnyi et al 1983;Lyon 1989;Ray and Hammerschmidt 1998;Zagoskina et al 2006;Baker et al 2008;Lerat et al 2009). Plants also produce inhibitors of virulence factors (Kim et al 2006).…”
Section: Bazan De Segura and Carpio (1974)mentioning
confidence: 97%
“…Susceptible cultivars produce non-uniform deposits of suberin making them less performing against pathogens (Finetti Sialer 1990;Ray and Hammerschmidt 1998). The anti-microbial agents produced by potatoes can be glycoalkaloids (α-chaconin and α-solanine), phenolic compounds and phytoalexins, antimicrobial compounds produced by the plant after pathogen attacks (Okopnyi et al 1983;Lyon 1989;Ray and Hammerschmidt 1998;Zagoskina et al 2006;Baker et al 2008;Lerat et al 2009). Plants also produce inhibitors of virulence factors (Kim et al 2006).…”
Section: Bazan De Segura and Carpio (1974)mentioning
confidence: 97%
“…S. ipomoeae also produces members of the thaxtomin family, the predominant of which is thaxtomin C (King et al 1994), and it appears that these compounds are also important for pathogenicity in this organism (G. Pettis, unpublished data). Thaxtomin induces a variety of phenotypic changes in the plant host including cell hypertrophy, root and shoot stunting, tissue necrosis, inhibition of cellulose (Duval et al 2005;Errakhi et al 2008;Fry and Loria 2002;Leiner et al 1996;Lerat et al 2009;Meimoun et al 2009;Scheible et al 2003;Tegg et al 2005). Recently, it was demonstrated that thaxtomin A reduces crystalline cellulose in the plant cell wall, it affects the expression of genes associated with cell wall synthesis, and it depletes cellulose synthase complexes from Arabidopsis seedling plasma membranes (Bischoff et al 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Scopoletin displays well‐recognized antimicrobial activities against various plant pathogens (Chong et al. 2002; Lerat et al. 2009), and we found that scopoletin, known to be efficient against Gram‐negative bacteria (Cespedes et al.…”
Section: Discussionmentioning
confidence: 93%